Monumental Harm : Reckoning with Jim Crow Era Confederate Monuments - Hartley, Roger C. (Book collections on Project MUSE., 2021)
"Professor of Law at Catholic University Roger C. Hartley provides a thorough overview of the issue of Confederate monuments and their problematic presence on the American landscape. He examines and dissects competing claims regarding the removal of these monuments from public spaces ... mov[ing] readers through various debates on the subject ...with the compelling logic of a legal scholar ... methodically build[ing] the case that 'Confederate monuments harm contemporary American society by perpetuating antiblack racial stereotyping and systemic racism.' This harm, he continues, 'overrides even good faith claims to leave Confederate monuments undisturbed in order to preserve Southern heritage.' In the course of building this case for material harm, Hartley nonetheless offers his own good faith discussions of competing arguments for retaining Confederate monuments in situ. While these include 'heritage' claims, they also include those sometimes heard from historians and historic preservationists regarding the significance of monuments as teaching tools and the dangers of 'sanitizing' the historical landscape. While Hartley's argument ultimately makes a compelling case for removal/relocation as the optimal choice, he does not dismiss the alternative arguments. Instead, he deconstructs each and examines them for potential flaws in a way that will force readers to examine their own beliefs"--